A thermodynamic entropy-based damage assessment with applications to prognostics and health management. (March 2018) - Imanian, Anahita; Modarres, Mohammad
To advance the traditional structural integrity and life estimation approach, this article presents an explanation of damage and develops an alternative approach to damage assessment based on the fundamental laws of thermodynamics. This explanation provides a new way to perform prognostics and health management in terms of the irreversible thermodynamic framework. Specifically, it is proposed and demonstrated that entropy generated due to material degradation can be used as an index of damage. It is claimed that the use of an entropy-based damage index offers a unified and more comprehensive measure of damage. This is because energy dissipation associated with failure mechanisms that lead to material degradation involves irreversible processes, resulting in entropy generation, which is physically measurable as the materials degrade. We therefore conclude that entropy generation can be used to assess the degree of damage, the amount of the life of materials expended, and the extent of the life remaining. As an application of the proposed concept, this article discusses the entropic characterization of the corrosion-fatigue degradation mechanism, in which a standard entropy-based damage prognostics and health management approach is employed in integrity assessment and remaining useful life prediction of aluminum 7075-T651 specimens. Using entropy as a thermodynamic state function for damage characterization is shown to be effective in handling the endurance threshold uncertainties for prediction purposes.